EFFECT OF PRODUCT QUALITY, PRICES AND SERVICES AGAINST PURCHASE DECISIONS AT PT. INDONESIAN DEPOT - Yesua Sandyarto Getrojaya H; Jayson Jayson; Erwin Erwin; Holfian Daulat Tambun Saribu (SEAN Institute, 2022)
This study aims to examine and analyze the effect of Product Quality, Price and Service on job satisfaction at PT. Indonesian Depot. The decrease in job satisfaction can be seen from employees who resign from the company. At PT. Depo Indonesia has a problem with company decisions, which can be seen from the sales targets that are not achieved at the company. On the quality of products owned by PT. Depo Indonesia still receives complaints from customers regarding the quality of its products, such as car spare parts, car lights, and others. The high price even though it is accompanied by the provision of a guarantee shows that the price given is still relatively high, as evidenced by the large number of buyers who only ask for the price. Service is part of service to customers that is carried out before and after purchase. However, in practice, there are still customers who are not satisfied, as can be seen from the number of purchases that have not been maximized. This study uses quantitative research with the sample used is 103 people. The data analysis method used multiple linear regression. Simple random sampling was used as a sampling method. In the t-test on product quality variables with values (2.124> 1.984), price (2.798> 1.984) and service quality (5.116> 1.984) partially positive and significant effect on purchasing decisions at PT. Indonesian Depot. In the F test, the variables of product quality, price and service quality showed a positive and significant influence with a value (20,482>2.70) on purchasing decisions at PT. Indonesian Depot This study uses quantitative research with the sample used is 103 people. The data analysis method used multiple linear regression. Simple random sampling was used as a sampling method. In the t-test on product quality variables with values (2.124> 1.984), price (2.798> 1.984) and service quality (5.116> 1.984) partially positive and significant effect on purchasing decisions at PT. Indonesian Depot. In the F test, the variables of product quality, price and service quality showed a positive and significant influence with a value (20,482>2.70) on purchasing decisions at PT. Indonesian Depot This study uses quantitative research with the sample used is 103 people. The data analysis method used multiple linear regression. Simple random sampling was used as a sampling method. In the t-test on product quality variables with values (2.124> 1.984), price (2.798> 1.984) and service quality (5.116> 1.984) partially positive and significant effect on purchasing decisions at PT. Indonesian Depot. In the F test, the variables of product quality, price and service quality showed a positive and significant influence with a value (20,482>2.70) on purchasing decisions at PT. Indonesian Depot In the t-test on product quality variables with values (2.124> 1.984), price (2.798> 1.984) and service quality (5.116> 1.984) partially positive and significant effect on purchasing decisions at PT. Indonesian Depot. In the F test, the variables of product quality, price and service quality showed a positive and significant influence with a value (20,482>2.70) on purchasing decisions at PT. Indonesian Depot In the t-test on product quality variables with values (2.124> 1.984), price (2.798> 1.984) and service quality (5.116> 1.984) partially positive and significant effect on purchasing decisions at PT. Indonesian Depot. In the F test, the variables of product quality, price and service quality showed a positive and significant influence with a value (20,482>2.70) on purchasing decisions at PT. Indonesian Depot